Molecular Signatures of Humic Acids from Different Sources as Revealed by Ultrahigh Resolution Mass Spectrometry. (1st April 2020) - Qin, Shuai; Xu, Chengbin; Xu, Yingzi; Bai, Yingchen; Guo, Fei
Abstract : Humic acid (HA) is extremely important for understanding the geochemical cycle of pollutants in different environments. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has performed molecular-level analysis of two standard HAs from the Suwannee River (SRHA) and leonardite (LEHA) and HA from Jiufeng forest in Beijing (JFHA), which is impossible for other conventional instruments. Regardless of the source of HA, compounds containing more heteroatoms (such as nitrogen and sulfur) have a higher degree of unsaturation and aromaticity. JFHA, SRHA, and LEHA from soil, river, and leonardite, respectively, are arranged in order from the lowest to highest degree of humification, according to molecular unsaturation and aromaticity of HAs. Soil HA is more labile and contains many large molecular weight compounds with low unsaturation. Regardless of unsaturation, molecules of River HA have a homogeneous molecular mass distribution and contain many plant-derived lignin- and tannin-like compounds, which are more stable than lipid and more labile than condensed aromatics. Leonardite HA with a high degree of humification contains a large number of compounds with high aromaticity and more heteroatoms and has low lability. Our results reveal the diversity of humic acid at molecular level because of different degree of humification and the lability. These conclusions are significant for understanding the role of humic acid from different sources in pollutant transformation and the geochemical cycle at the molecular level.